Generation of 2′,3′-Cyclic Phosphate-Containing RNAs as a Hidden Layer of the Transcriptome - Shigematsu, Megumi; Kawamura, Takuya; Kirino, Yohei (Frontiers in Genetics, 2018)
Cellular RNA molecules contain phosphate or hydroxyl ends. A 2′,3′-cyclic phosphate (cP) is one of the 3′-terminal forms of RNAs mainly generated from RNA cleavage by ribonucleases. Although transcriptome profiling using RNA-seq has become a ubiquitous tool in biological and medical research, cP-containing RNAs (cPRs) form a hidden transcriptome layer, which is infrequently recognized and characterized, because standard RNA-seq is unable to capture them. Despite cPRs’ invisibility in RNA-seq data, increasing evidence indicates that they are not accumulated simply as non-functional degradation products; rather, they have physiological roles in various biological processes, designating them as noteworthy functional molecules. This review summarizes our current knowledge of cPR biogenesis pathways and their catalytic enzymatic activities, discusses how the cPR generation affects biological processes, and explores future directions to further investigate cPR biology.